Technology Adaptation through Digital Applications in Introducing Traditional Madura Games - Fikri Nazarullail; Dwi Nurhayati Adhani (Universitas Muhammadiyah Ponorogo, 2023)
Traditional game isan ancestral heritage that deserves to be preserved as a form of appreciation for the insights of Nusantara. Traditional games have almost the same characteristics among regions in Nusantara. Traditional games are increasingly disappearing, making us as educators have a part to play in preserving them through learning activities in the classroom. Therefore, traditional games must continue to be developed into application-based games. The research method used in this study used a development research approach with ten research stages. The subject of this study included the Kindergarten unit on the south coast of Bangkalan Regency, which applies traditional games in learning. The study results showed that the digital game developed was feasible and required revision to perfect the application. The results of the trials carried out in the three settings also showed Good criteria, so this application is suitable for use in learning in children aged 4-5 years at school or home.